Investigation into the pharmacodynamics and pharmacokinetics of recombinant human interferon alfa-2b vaginal suppository following process optimization in chinese rhesus macaque - Xueyan Zhang; Baisong Zhou; Yihan Gong; Yulin Liu (Scientific Reports)
Abstract Recombinant human interferon Alfa-2b vaginal suppository is a gynecological preparation mainly made of interferon, commonly used to treat diseases related to viral infections such as cervical erosion. As a recombinant protein drug, it is important to pay attention to the possibility of modifications that may lower the quality of the drug during the production process. The aim of this study is to evaluate the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of this product in Chinese rhesus macaque after purification process changes, and to demonstrate that there is no difference in the biological activity of recombinant human interferon Alfa-2b vaginal suppository stock solution before and after process changes. There are 12 test animals: Chinese rhesus macaques who received a two-group crossover design and were subcutaneously injected with the same active dose of 500,000 IU/kg around the navel in the abdomen. According to maximum concentration (Cmax) and time of maximum concentration (Tmax) within non-parametric test (P > 0.05), geometric mean ratio of PK parameter Cmax for the drugs after purification process changes (sample S) compared to the before purification process changes one (sample R) was 97.09%, with a 90% confidence interval (CI) of 87.39–107.87%. The geometric mean ratio Cmax of serum Beta2-microglobulin (PDmax) for PD index is 100.07%, with a 90% CI of 97.16–103.07%; Geometric mean ratio of AUEC0 − t is 98.91%, with a 90% CI of 96.53–101.34%. The geometric mean of the PD index, neopterin PDmax, is 97.75%, with a 90% CI of 92.53–103.25%; Geometric mean of AUEC0 − t is 105.59%, with a 90% CI ranging from 97.22 to 114.68%. The important parameters of PK/PD meet the equivalence requirements, and biological activity of the recombinant human interferon Alfa-2b vaginal suppository stock solution after purification process change is no different from before the change. Under the same active dose administration conditions, the same biological effects were produced, achieving the same effect as before the change.